Factors Predicting Intention to Give Waqf in Agriculture Sector - Mahri, A Jajang. W; Juliana, Juliana; Muhammad, Mumuh; Hardiansyah, Kiki; Rosida, Rida; Oroji, Ahmad Muhammad (Review of Islamic Economics and Finance, 2024)
Purpose - this study is to analyze the Muslim community’s intention to provide waqf for the agricultural sector using Islamic religiosity variable, variables in the theory of planned behavior and variable of waqf knowledge.Design / Methodology / Approach - this study is survey method with quantitative approach and Partial Least Square-Structural Equation Modeling (PLS-SEM) as analysis tool. This study processes data from the questionnaires distributed to 574 respondents living in various provinces as samples.Findings – the study show that all exogenous variables have a positive effect on endogenous variables, except for Islamic religiosity. Apart from that, the attitude variable is able to mediate the positive influence of the level of Islamic religiosity on intentions to give waqf in the agricultural sector.Practical Implications– This research makes a significant contribution to the literature on productive waqf and can be a reference for stakeholders in developing waqf programs in Indonesia, especially in the agricultural sector which has great potential but has not been utilized optimally.Originality/Value– This research fills a gap in the existing literature by examining waqf intentions in the agricultural sector, an area that has been minimally researched previously. In addition, this research modifies and expands the use of the Theory of Planned Behavior (TPB) by including the waqf knowledge variable to better understand the intentions of the Indonesian Muslim community in providing waqf in the agricultural sector.